Election Management Bodies in East Africa - Makulilo, Alexander B.; Osodo, Patrick Okoth; Sekaggya, Margaret; Ang'ila, Francis; Ntaganda, Eugene (Book collections on Project MUSE., 2016)
The management of elections is increasingly generating impassioned debate in these East African nations - Burundi, Kenya, Rwanda, Tanzania and Uganda. The bodies that manage and conduct elections are, therefore, coming under intense citizen and stakeholder scrutiny for the manner in which they are composed, how they organise and perform their mandates, and the outcomes they achieve. The effectiveness of electoral management bodies (EMBs) has largely been influenced by the impact of political violence on election management reforms in East Africa. Even in countries where EMBs are the products of reforms initiated in the aftermath of violent disputes over elections, they still face enormous challenges in dealing with electoral disputes and anticipating election-related crises. Although changes to constitutions and the laws in these countries have sought to make EMBs independent and, therefore, more inclined to deliver free, fair and credible elections, there are many issues that determine their impartiality and their ability to allow for the aggregation and free expression of the will of the people. These shortcomings negatively impact on democracy. This volume assembles case studies on the capacity of EMBs in these five East African countries to deliver democratic and transparent elections.